2022
DOI: 10.3390/su14148435
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Coffee Silverskin through Subcritical Water Extraction: An Optimization Based on T-CQA Using Response Surface Methodology

Abstract: Coffee silverskin (CS) is the only byproduct of the roasting process for coffee beans and is rich in phenolic compounds with various bioactivities. This study proposes a valorization option for bioactive compounds (T-CQA) based on a subcritical water extraction (SWE) technique, which is known for its high efficiency and feasibility for use on an industrial scale. The use of water as a sole solvent requires a minimum number of cleaning steps and renders the extract safe for further applications, such as in eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The addition of plant extracts into the meat matrix can be difficult if their color and flavor are not suitable for meat and if their solubility is insufficient, generating unpleasant spots in the final product [ 29 , 30 ]. Some authors investigated the effectiveness of the subcritical water extraction (SWE) method for the recovery of water-soluble phenolic compounds from medicinal plants and coffee by-products [ 31 , 32 ], as well as the possibility of producing plant extracts that can be used as natural antioxidant ingredients in pharmaceuticals, cosmetics, and food [ 33 , 34 , 35 , 36 ]. During the last decade, some studies have reported increased oxidative stability and improved functional properties of food products prepared with extracts from green coffee beans, which are rich in polyphenols [ 27 , 37 , 38 ], but there are not results on their use as an ingredient in pork meat.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of plant extracts into the meat matrix can be difficult if their color and flavor are not suitable for meat and if their solubility is insufficient, generating unpleasant spots in the final product [ 29 , 30 ]. Some authors investigated the effectiveness of the subcritical water extraction (SWE) method for the recovery of water-soluble phenolic compounds from medicinal plants and coffee by-products [ 31 , 32 ], as well as the possibility of producing plant extracts that can be used as natural antioxidant ingredients in pharmaceuticals, cosmetics, and food [ 33 , 34 , 35 , 36 ]. During the last decade, some studies have reported increased oxidative stability and improved functional properties of food products prepared with extracts from green coffee beans, which are rich in polyphenols [ 27 , 37 , 38 ], but there are not results on their use as an ingredient in pork meat.…”
Section: Introductionmentioning
confidence: 99%
“…43 Subcritical water was also employed by Ginting et al , targeting chlorogenic acids, reaching a percentage of 0.27% (w/w dry CS) at 147.8 °C. 44…”
Section: Resultsmentioning
confidence: 99%
“…43 Subcritical water was also employed by Ginting et al, targeting chlorogenic acids, reaching a percentage of 0.27% (w/w dry CS) at 147.8 °C. 44 The solvent-based extraction was supposed to be exhaustive in chlorogenic acids' complete extraction from both the delipidized biomasses. Aer assessing for consistency the effectiveness of the extraction of chlorogenic acids from GCB and CS with solvents with the literature, data were assumed to represent the reference when studying the recovery of the same phenolics by means of supercritical uids.…”
Section: Delipidization Extraction Yields and Kineticsmentioning
confidence: 99%
“…In recent years, one of the most efficient methods of TPC extraction is subcritical water extraction. With the use of this method, Ginting et al [69] obtained above 51 mg GAE/g CS, which is a significantly higher yield in comparison to conventional methods.…”
Section: Optimization Of the Extraction Conditionsmentioning
confidence: 97%